Adjuvant Chemotherapy in Resected Lung Cancer: Two-Year Experience in a University Hospital. Issue 5 (2008) - Bouchard, Nicole; Laberge, Francis; Raby, Bruno; Martin, Sylvie; Lacasse, Yves
Abstract : BACKGROUND: Randomized trials have confirmed the benefits of adjuvant chemotherapy in improving survival in resected early-stage non-small-cell lung cancer (NSCLC). The extent to which these results have translated into clinical practice is unknown. OBJECTIVE: To examine the referral pattern of patients with resected lung cancer to adjuvant chemotherapy, and to compare compliance and toxicities with current literature. METHODS: A retrospective analysis of all patients who underwent a surgical resection for lung cancer at Laval Hospital (Quebec City, Quebec) from March 2004 to January 2006 was conducted. RESULTS: A total of 258 patients underwent surgery. Seven patients were excluded because of early postoperative death, and two patients were excluded because of incomplete data. Data from 249 patients were analyzed (94% NSCLC). Fifty per cent were referred to medical oncology for consideration of adjuvant chemotherapy, including 37 of 61 patients with stage II NSCLC. One hundred patients received chemotherapy. No significant difference in age, sex, comorbidities and surgical procedures was observed between those who received chemotherapy and those who did not. Chemotherapy was initiated 47 days (median) after the surgery and consisted mainly of cisplatin-vinorelbine (38%), cisplatin-etoposide (22%) and carboplatin-paclitaxel (20%). Sixty-six per cent of the patients completed all four cycles. Grade 3 or 4 toxicities consisted mainly of fatigue (23%) and cytopenia (40%). No death was registered; 15% had to be hospitalized because of adverse effects. CONCLUSION: Although adjuvant chemotherapy is gaining acceptance in clinical practice, more patients should be referred to medical oncology following surgical resection. Compliance and toxicity are similar to or better than those described in published randomized trials.